Pharmaceutical Supply Chains - Medicines Shortages - Barbosa-Povoa, Ana Paula; Jenzer, Helena; de Miranda, João Luís.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an insight of relevant case studies and updated practices in "Pharmaceutical Supply Chains" (PharmSC) while addressing the most relevant topics within the COST Action "Medicines Shortages" (CA15105). The volume focuses on the most recent developments in the design, planning and scheduling of PharmSC, broadening from the suppliers' selection to the impact on patients and healthcare systems, addressing uncertainty and risk mitigation, and computational issues. It is directed at MSc/PhD students and young researchers (Post-Docs) in Pharmaceutics/Pharmaceutical sciences, Engineering fields, Economics/Management, as well as pharmaceutical decision makers, managers, and practitioners, and advanced readers demanding a fresh approach to decision making for PharmSC. The contributed chapters are associated with the homonymous COST Training Schools (TS), and the book creates a better understanding of the Action "Medicines Shortages" challenges and opportunities.
From the contents: The European Medicines Shortages Research Network and its mission to strategically debug disrupted pharmaceutical supply chains -- Design and Planning of Sustainable Vaccine Supply Chains -- Drug shortages and their impact on patients and health care system - how can systemic and organizational frameworks help to prevent or mitigate them? -- Patient perspective: reporting on medicines shortages - hemophilia A case in Latvia -- Shortages of Medicines originating from manufacturing -- Risk Mitigation and Preventing Medicines Shortages -- An Exploratory Assessment of Risk and Resilience in Pharmaceutical Supply Chains -- Review of Pharmaceutical Sea Freight and Malaysian Third-Party Logistics Service Providers - a Supply Chain Perspective -- The needs and barriers within the Supply Chain actors - Hospital Pharmacy needs -- Patients Perspectives on Medicines Shortages in Hospital Setting.
Keywords: Pharmaceutical chemistry; Industrial Management; Business logistics; Pharmaceutics; Industrial Management; Supply Chain Management